Threats or violence from patients was associated with turnover intention among foreign-born GPs - a comparison of four workplace factors associated with attitudes of wanting to quit one's job as a GP - Mari Eneroth; Marie Gustafsson Sendén; Karin Schenck Gustafsson; Maja Wall; Ann Fridner (Taylor & Francis Group, 2017)
Objective: General practitioners (GPs) are crucial in medical healthcare, but there is currently a shortage of GPs in Sweden and elsewhere. Recruitment of GPs from abroad is essential, but foreign-born physicians face difficulties at work that may be related to turnover intention, i.e. wanting to quit one's job. The study aims to explore the reasons to why foreign-born GPs may intend to quit their job. Design: Survey data were used to compare four work-related factors that can be associated with turnover intentions; patient-related stress, threats or violence from patients, control of work pace, and empowering leadership, among native-born and foreign-born GPs. These work-related factors were subsequently examined in relation to turnover intention among the foreign-born GPs by means of linear hierarchical regression analyses. The questionnaire consisted of items from the QPS Nordic and items constructed by the authors. Setting: A primary care setting in a central area of Sweden. Subjects: Native-born (n = 208) and foreign-born GPs (n = 73). Results: Turnover intention was more common among foreign-born GPs (19.2% compared with 14.9%), as was the experience of threats or violence from patients (22% compared with 3% of the native-born GPs). Threats or violence was also associated with increased turnover intention. Control of work pace and an empowering leadership was associated with reduced turnover intention. Practice implications: The organisations need to recognise that foreign-born GPs may face increased rates of threats and/or violence from patients, which may ultimately cause job turnover and be harmful to the exposed individual.